Coefficients Estimates of the Class of Biunivalent Functions. (8th March 2016) - Aljouiee, Abdullah; Goswami, Pranay
Abstract : Applying the Faber polynomial expansions, we obtain the general coefficient bounds for the class of biunivalent functions with bounded boundary rotations.